Fish Processing Using Geothermal Sources in Village Idamdehe West Halmahera District North Maluku Province - Abdurrachman Baksir; Kadri Daud; Eko Setyabudi Wibowo; Nebuchadnezzar Akbar; Irfan Haji (Jurnal Pengolahan Hasil Perikanan Indonesia, 2018)
Idamdehe village has geothermal potential that can be used for fish processing. However, until now the use of this potential has not been carried out optimally. Geothermal in this area is only used as a touristattraction for local people to visit. However, utilization for fisheries processing has not been carried out. This research aimed to observe the use of geothermal in fisheries processing. The research method was carried out with different treatments, including traditional and conventional methods. Fish samples used for processing were yellowstrip scad fish (Selaroides leptolepis). The results of the study showed the value of geothermal vapor temperature increased along with the increase of the depth of excavation, namely in 20 cm with a temperature value of 90oC, a depth of 30 cm with a temperature of 100oC. The process of fish processing using geothermal steam only took 30 minutes with a temperature of 100oC, while the conventional method using geothermal steam took 1 hour with a temperature of 100oC.